Differences in the SNARE evolution of fungi and metazoa. (22nd July 2009) - Kienle, Nickias; Kloepper, Tobias H.; Fasshauer, Dirk
Abstract : Proteins of the SNARE (soluble N -ethylmaleimide-sensitive factor-attachment protein receptor) family are key factors in all vesicle-fusion steps in the endocytic and secretory pathways. SNAREs can assemble into a tight four-helix bundle complex between opposing membranes, a process that is thought to pull the two membranes into close proximity. The complex-forming domains are highly conserved, not only between different species, but also between different vesicular trafficking steps. SNARE protein sequences can be classified into four main types (Qa, Qb, Qc and R), each reflecting their position in the four-helix bundle. Further refinement of these main types resulted in the identification of 20 distinct conserved groups, which probably reflect the original repertoire of a proto-eukaryotic cell. We analysed the evolution of the SNARE repertoires in metazoa and fungi and unveiled remarkable differences in both lineages. In metazoa, the SNARE repertoire appears to have undergone a substantial expansion, particularly in the endosomal pathways. This expansion probably occurred during the transition from a unicellular to a multicellular lifestyle. We also observed another expansion that led to a major increase of the secretory SNAREs in the vertebrate lineage. Interestingly, fungi developed multicellularity independently, but in contrast with plants and metazoa, this change was not accompanied by an expansion of the SNARE set. Our findings suggest that the rise of multicellularity is not generally linked to an expansion of the SNARE set. The structural and functional diversity that exists between fungi and metazoa might offer a simple explanation for the distinct evolutionary history of their SNARE repertoires.